PROBLEMS OF VERIFYING THE AUTHENTICITY OF ASYLUM SEEKERS' DOCUMENTS AND IMPROVING THE IDENTIFICATION OF THESE PERSONS - Šnipa, Inna; Arbidane, Iluta; Volkova, Jeļena (Border Security and Management, 2020)
The Republic of Latvia must be ready to implement the asylum procedure quickly and efficiently, improving the identification process, as the influx of asylum seekers into the EU may recur. The aim of the research is to study the asylum seekers identification procedure, the factors affecting it, and the possibilities for improving this procedure, to determine nature of the authentication process of documents presented by asylum seekers, to identify authentication problems and to find possible solutions. As a result of the research, the authors have evaluated the process of asylum seekers identification and developed proposals for its improvement, described the factors affecting the authentication of asylum seekers' documents and evaluated the possibilities to exclude these factors. The method of scientific induction, graphical method, document analysis, monographic or descriptive method are used in the research.